2016
DOI: 10.4269/ajtmh.16-0144
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy and Tolerability of Artesunate–Azithromycin for the Treatment of Falciparum Malaria in Vietnam

Abstract: Abstract. Safe and effective antimalarial drugs are required for the treatment of pregnant women. We report a 3-day regimen of artesunate (4 mg/kg/day)-azithromycin (25 mg/kg/day) (ASAZ) to be efficacious (polymerase chain reactioncorrected cure rate of 96.7%) and well tolerated in the treatment of Plasmodium falciparum malaria in children (N = 11) and adults (N = 19), in Vietnam in 2010. In comparison, the cure rate for artesunate (4 mg/kg on day 0, 2 mg/kg on days 1-6) was 90.0% in children (N = 7) and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…As is the case with some other antibiotics, azithromycin acts against the parasite apicoplast and exerts slow antimalarial activity [6]. In clinical trials, azithromycin has been found to improve the treatment efficacy of both artesunate and chloroquine relative to each agent alone [4, 5, 11]. Azithromycin has also been shown to prevent malaria infections, although its efficacy appears to be inferior to that of doxycycline [2, 3].…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with some other antibiotics, azithromycin acts against the parasite apicoplast and exerts slow antimalarial activity [6]. In clinical trials, azithromycin has been found to improve the treatment efficacy of both artesunate and chloroquine relative to each agent alone [4, 5, 11]. Azithromycin has also been shown to prevent malaria infections, although its efficacy appears to be inferior to that of doxycycline [2, 3].…”
Section: Discussionmentioning
confidence: 99%
“…When given alone, daily azithromycin had only modest prophylactic efficacy against malaria infection in Kenyan and Indonesian adults (23,24) and against vivax malaria in Thai adults (25). Though azithromycin is not used alone for malaria treatment, its combination with chloroquine or artesunate offered excellent clinical efficacies in some trials (26,27). Both naphthoquine and azithromycin have excellent safety profiles, and their in vitro interactions on P. falciparum parasites were synergistic (28).…”
mentioning
confidence: 99%
“…However, it has been considered as a potential candidate for combination therapy, especially in pregnant women and children, owing to its multistage targeting action with unique mechanism, attractive safety profile, and excellent pharmacological properties (20,23). AZ combination therapy with other antimalarials has been evaluated extensively in clinical trials over the past dozen years, but no reliable evidence has been found on the superiority or equivalence of AZ combination therapy with current partner drugs compared to the current first-line antimalarial combinations (22,(24)(25)(26)(27)(28)(29)(30). A more appropriate partner for AZ in combination remains to be identified.…”
mentioning
confidence: 99%